Core fucose is essential glycosylation for CD14-dependent Toll-like receptor 4 and Toll-like receptor 2 signalling in macrophages. (15th November 2018) - Nakayama, Kotarosumitomo; Wakamatsu, Kana; Fujii, Hironobu; Shinzaki, Shinichiro; Takamatsu, Shinji; Kitazume, Shinobu; Kamada, Yoshihiro; Takehara, Tetsuo; Taniguchi, Naoyuki; Miyoshi, Eiji
Abstract: Core fucosylation, catalysed by α-1, 6 fucosyltransferase (FUT8), regulates growth factor receptors in immune function. Although core fucose regulates many immune cell types, few reports confront the association between core fucose activity and an innate immune reaction. Here, we have investigated the function of core fucose in macrophages in vivo and in vitro using Fut8 -deficient mice and cells. Following lipopolysaccharide (LPS) stimulation, inflammatory cytokine production in Fut8 -deficient ( Fut8 −/− ) macrophages was suppressed in both in vivo and in vitro experiments. Because LPS is recognized by Toll-like receptor 4 (TLR4), which induces the signalling cascade, TLR4 signalling was assumed to be impaired in Fut8 −/− cells. Flow cytometry analyses revealed, however, that a lack of core fucose reduced the expression of, not TLR4, but CD14, which is necessary for TLR4 endocytosis. Because CD14 is necessary for TLR2 signalling, the immune response of TLR2 was also impaired in Fut8 −/− macrophages. Moreover, in the dextran sodium sulphate (DSS)-induced murine colitis model, the mice grafted with Fut8 −/− bone marrow cells exhibited higher resistance to inflammation than those grafted with Fut8 +/+ bone marrow cells. These findings indicate that core fucose is essential for CD14-dependent TLR4 and TLR2 signalling in murine macrophage activity, leading to DSS-induced experimental colitis.